The Impacts of the COVID-19 Traffic Light System on Staff in Tertiary Education in New Zealand - Taylor L-A; Reid J; Jagroop-Dearing A (MDPI, Basel, Switzerland, 2024)
The global impact of the COVID-19 pandemic demanded a swift transition in the usual educational mode of delivery from face to face to online. New Zealand established “a traffic light system” after initial COVID-19 lockdowns, and educational delivery adapted accordingly at a tertiary education provider in Te Pūkenga, Eastern Institute of Technology. This study investigates the ramifications of the traffic light system on this institute’s staff, employing semi-structured interviews and an inductive semantic thematic analysis. The findings reveal a universal impact on staff, characterized by an augmented workload attributed to students’ absences and illnesses. This led to increased support demands of staff for their students’ academic progression. Anxiety, stress, and guilt emerged as prevalent emotions linked to student support. Despite the staff adapting to the mandates, a notable challenge arose from the discord between educational and industry directives, causing confusion among the students. While the study indicates staff resilience in navigating the traffic light changes, it underscores the imperative of recognizing the toll on their wellbeing. The research calls for a proactive consideration of future challenges, emphasizing the importance of safeguarding the mental and emotional health of tertiary education staff amidst potential uncertainties in educational delivery.
Keywords: COVID-19; mandates; traffic light system; education; pastoral support; wellbeing